Environment-friendly noise-reducing PC / ASA composite material for sound production, and preparation method and application thereof
Patent Information
- Application Number
- CN202611054653.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-09
AI Technical Summary
本发明的环保降噪PC/ASA音响用复合材料既解决了塑料经过长时间暴露在阳光下可能导致颜色褪色或强度下降、吸声性能较差、易产生共振的问题;又解决了木材易吸水变形导致尺寸稳定性差、自身耐热性较差、在与塑料进行共混过程中易发生分解碳化,造成音箱制品外观颜色变深、力学强度显著下降等问题
(1)具有优异的耐光热老化性能:本发明选用PC树脂/ASA树脂作为基材,结合了PC树脂的热稳定性和ASA树脂的耐光老化性能。PC树脂/ASA树脂不仅具有较高的强度和抗冲击性能,能有效抵御外界的碰撞和摩擦,还具备出色的耐候性,无论是在高温、低温、潮湿还是紫外线辐射较强的环境下,PC树脂/ASA树脂都能保持稳定的性能,不易出现变形、褪色、脆化等问题。同时,通过对竹纤维的乙酰化处理,用乙酰基部分取代羟基,显著提升了竹纤维的热稳定性;同时使用具有片层结构的蒙脱土作为耐热剂,用来阻隔热量的传递和降解产物的扩散,以此来提高竹纤维的稳定性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material reinforcement technology, specifically relating to an environmentally friendly noise-reducing PC / ASA audio composite material, its preparation method, and its application. Background Technology
[0002] The choice of speaker enclosure material has a crucial impact on the overall performance and appearance of the speaker. Currently, common speaker enclosure materials on the market include plastic, metal, and wood. Metal enclosures are generally made of aluminum alloy, which has advantages such as durability and good heat insulation; however, it is expensive and can only be used in high-end speakers. Wood has good natural damping properties, which gives wooden speakers a warm, natural tone; however, wooden speakers have high manufacturing costs and are prone to warping and cracking due to moisture. Plastic enclosures are the mainstream in the market today. Compared to metal and wood, plastic enclosures are relatively inexpensive, lighter, and less susceptible to moisture or damage. However, plastic enclosures also have some drawbacks. On the one hand, their durability is insufficient; when exposed to light and heat environments (such as direct sunlight or proximity to heat-generating equipment) for extended periods, they are prone to deformation, cracking, and other structural failures. On the other hand, their damping performance is poor, making it difficult to effectively dissipate vibration energy. This causes multi-frequency sound waves (especially low frequencies) inside the speaker to leak outwards disorderly through the enclosure, superimposing and interfering with the sound output from the front of the speaker, ultimately resulting in sound quality distortion. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides an environmentally friendly noise-reducing PC / ASA speaker composite material, its preparation method, and its applications. This invention combines plastic and wood to obtain an environmentally friendly noise-reducing PC / ASA speaker composite material that possesses both the natural, mellow sound quality of wooden speakers and the lightweight, waterproof, and low-cost advantages of plastic speakers. This environmentally friendly noise-reducing PC / ASA speaker composite material solves the problems of plastic fading or strength reduction, poor sound absorption, and resonance caused by prolonged exposure to sunlight; it also solves the problems of wood's poor dimensional stability due to water absorption and deformation, poor heat resistance, and decomposition and carbonization during blending with plastic, resulting in darkening of the speaker product's appearance and a significant decrease in mechanical strength.
[0004] The objective of this invention is achieved through the following technical solution: An environmentally friendly noise-reducing composite material for PC / ASA audio equipment, the composite material comprising the following components in parts by weight: 30-40 parts by weight of PC resin, 20-30 parts by weight of ASA resin, 10-20 parts by weight of SAN resin, 5-10 parts by weight of silicone aerogel, 15-25 parts by weight of bamboo fiber, 0.2-0.5 parts by weight of stabilizer, 0.2-0.5 parts by weight of antioxidant, 1-2 parts by weight of heat resistant agent, 3-5 parts by weight of compatibilizer, and 0.5-1 parts by weight of processing aid.
[0005] According to an embodiment of the present invention, the composite material comprises 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, or 40 parts by weight of PC resin.
[0006] According to an embodiment of the present invention, the composite material comprises 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, or 30 parts by weight of ASA resin.
[0007] According to an embodiment of the present invention, the composite material comprises 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight of SAN resin.
[0008] According to an embodiment of the present invention, the composite material comprises 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight of silica aerogel.
[0009] According to an embodiment of the present invention, the composite material comprises 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, or 25 parts by weight of bamboo fiber.
[0010] According to an embodiment of the present invention, the composite material includes 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, or 0.5 parts by weight of a stabilizer.
[0011] According to an embodiment of the present invention, the composite material includes 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, or 0.5 parts by weight of an antioxidant.
[0012] According to an embodiment of the present invention, the composite material comprises 1 part by weight, 1.1 part by weight, 1.2 part by weight, 1.3 part by weight, 1.4 part by weight, 1.5 part by weight, 1.6 part by weight, 1.7 part by weight, 1.8 part by weight, 1.9 part by weight, or 2 parts by weight of a heat-resistant agent.
[0013] According to an embodiment of the present invention, the composite material comprises 3 parts by weight, 3.2 parts by weight, 3.5 parts by weight, 3.6 parts by weight, 3.8 parts by weight, 4 parts by weight, 4.2 parts by weight, 4.4 parts by weight, 4.5 parts by weight, 4.6 parts by weight, 4.8 parts by weight, or 5 parts by weight of a compatibilizer.
[0014] According to an embodiment of the present invention, the composite material includes 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, or 1 part by weight of processing aid.
[0015] According to an embodiment of the present invention, the PC resin is a silicon copolymer bisphenol A type polycarbonate resin, wherein the mass percentage of silicon is 5%-10%, for example, 5%, 6%, 7%, 8%, 9% or 10%.
[0016] According to an embodiment of the present invention, the melt index of the PC resin at 300°C / 1.2kg is 8-20g / 10min, for example, 8g / 10min, 10g / 10min, 12g / 10min, 15g / 10min, 18g / 10min or 20g / 10min.
[0017] According to an embodiment of the present invention, the PC resin is prepared by a method known in the art, or is obtained through commercial purchase, such as general-purpose PC resin purchased from Covestro, SABIC, or Wanhua Chemical, such as PC resin products with brand names 2805, 2807, and 2605 purchased from Covestro, PC resin products with brand names EXL1414 and PC6100 purchased from SABIC, and PC resin products with brand names ME07 / ME10 purchased from Wanhua Chemical, etc.
[0018] According to an embodiment of the present invention, the ASA resin is an organosilicon-modified acrylonitrile-styrene-acrylate graft copolymer, wherein the mass percentage of acrylate is 50-70%, for example, 50%, 55%, 60%, 65% or 70%.
[0019] According to an embodiment of the present invention, the ASA resin is prepared by a method known in the art, or is obtained through commercial purchase, such as ASA resin products with the grades S797SE and S778T purchased from INEOS, ASA resin products with the grades Geloy XTW200 and Geloy FXTW30CP purchased from SABIC, ASA resin products with the grades LI911 and LI913 purchased from LG Chem, and ASA resin products with the grades LP2083, LP2072, and LP2075 purchased from Guangzhou Entropy Energy Co., Ltd., etc.
[0020] According to an embodiment of the present invention, the SAN resin is an acrylonitrile-styrene copolymer resin, wherein the mass percentage of acrylonitrile is 20%-30% and the mass percentage of styrene is 70%-80%. The number average molecular weight of the SAN resin is 100,000-200,000. The melt index of the SAN resin at 220℃ / 10kg is 50-70g / 10min, for example, 50g / 10min, 55g / 10min, 60g / 10min, 65g / 10min or 70g / 10min.
[0021] According to an embodiment of the present invention, the SAN resin is prepared by a method known in the art, or is obtained through commercial purchase, such as SAN resin products with the grades Luran 338L, Luran 348Q, and Luran 358N purchased from INEOS, SAN resin products with the grades 81HF, 80HF, 82TR, and 95HCTC purchased from LG Chem, and SAN resin products with the grades AS-100 and AS-200 purchased from Yangzi Petrochemical, etc.
[0022] According to an embodiment of the present invention, the silica aerogel is a silica aerogel. The pore size of the silica aerogel is 20-50 nm, for example, 20 nm, 30 nm, 40 nm, or 50 nm. The porosity of the silica aerogel is 90-95%. The silica aerogel possesses a nanoscale porous structure (pore size 20-50 nm) and extremely high porosity (90-95%), which allows it to absorb sound waves through air viscosity resistance and pore resonance, effectively improving the sound absorption and noise reduction effect of the composite material. Simultaneously, the silica aerogel exhibits good thermal stability and weather resistance, which greatly improves the photothermal aging resistance of the composite material. Furthermore, the silica aerogel can fill the gaps between the bamboo fibers that serve as a supporting framework, effectively reducing damage to the silica aerogel during processing and fully utilizing its functional effects.
[0023] According to an embodiment of the present invention, the silica aerogel is prepared by a method known in the art, or is obtained through commercial purchase, such as silica aerogel products of the AG-DC series purchased from Shenzhen Zhongning Technology Co., Ltd., silica aerogel products of the NANO-SA40 series purchased from Shaoxing Nano Technology Co., Ltd., silica aerogel products of the HUALU AG-DH series purchased from China Chemical Hualu New Materials Co., Ltd., etc.
[0024] According to an embodiment of the present invention, the bamboo fiber is acetylated bamboo fiber, wherein the degree of acetylation (DS) is 0.5-0.8, for example, 0.5, 0.6, 0.7 or 0.8. The length of the bamboo fiber is 1-5 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm; the diameter of the bamboo fiber is 10-50 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm or 50 μm. The bamboo fiber has a large aspect ratio, good flexibility, and a surface covered with grooves and micropores, which can form a large number of interconnected tortuous microporous channels in the composite system, which can reflect and scatter sound waves multiple times, thereby improving the sound absorption and noise reduction effect of the composite material. The bamboo fiber has a very low lignin content and also contains natural bamboo quinone (antioxidant component), resulting in better resistance to ultraviolet aging. The bamboo fiber is acetylated bamboo fiber with a degree of acetylation (DS) of 0.5-0.8. The acetyl groups partially replace the hydroxyl groups, which ensures that the bamboo fiber contains hydroxyl groups, giving it hydrophilicity, and also ensures that the bamboo fiber contains acetyl groups, significantly improving the thermal stability of the bamboo fiber. At the same time, it retains the mechanical properties of the bamboo fiber, allowing it to exist as a skeleton support in the composite material, thereby improving the photothermal aging resistance of the composite material.
[0025] According to an embodiment of the present invention, the acetylated bamboo fiber is prepared by the following method: (1) Remove impurities from bamboo fibers, wash and dry until the moisture content of bamboo fibers is ≤5%; (2) Mix dried bamboo fiber, acetic anhydride and p-toluenesulfonic acid and react them; after reacting for a period of time, add deionized water to terminate the reaction; (3) The bamboo fiber after the reaction was washed and dried with deionized water to prepare the acetylated bamboo fiber.
[0026] According to an embodiment of the present invention, in step (1), the impurities in the bamboo fiber are, for example, bamboo chips or dust.
[0027] According to an embodiment of the present invention, in step (1), the cleaning is, for example, rinsing with deionized water 3-5 times until the rinsing solution is neutral (e.g., pH=6.5-7.5).
[0028] According to an embodiment of the present invention, in step (1), the drying is performed in an oven at 60-80°C for 8-24 hours.
[0029] According to an embodiment of the present invention, in step (1), controlling the moisture content of bamboo fiber to ≤5% can effectively prevent moisture from affecting the efficiency of the acetylation reaction.
[0030] According to an embodiment of the present invention, in step (2), the mass ratio of bamboo fiber to acetic anhydride is 1:5-12, for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12.
[0031] According to an embodiment of the present invention, in step (2), the mass ratio of bamboo fiber to p-toluenesulfonic acid is 1:0.01-0.05, for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04 or 1:0.05.
[0032] According to an embodiment of the present invention, in step (2), the mixing is carried out, for example, under stirring conditions, and the stirring speed is 300-500 rpm.
[0033] According to an embodiment of the present invention, in step (2), the reaction is carried out under nitrogen protection.
[0034] According to an embodiment of the present invention, in step (2), the temperature of the reaction is 60-90°C; and the reaction time is 5-12 hours.
[0035] According to an embodiment of the present invention, in step (2), the amount of deionized water added is 2-3 times the volume of the reaction liquid. The addition of deionized water can consume the remaining unreacted acetic anhydride (converting acetic anhydride into acetic acid). After adding deionized water, the reaction is terminated by stirring for 30 minutes.
[0036] According to an embodiment of the present invention, in step (3), the bamboo fiber is repeatedly rinsed with deionized water until the pH of the filtrate is 6-7 (the purpose is to remove residual acetic anhydride and acetic acid).
[0037] According to an embodiment of the present invention, in step (3), the drying is carried out in a vacuum oven at 60-70°C for 8-12 hours. Under these conditions, the acetyl groups can be effectively removed due to high temperature, and the moisture content of the acetylated bamboo fiber can be controlled to be 3%-5%.
[0038] According to an embodiment of the present invention, the stabilizer is a mixture of zinc oxide and zinc sulfide, preferably a mixture of zinc oxide and zinc sulfide in a mass ratio of 1:1. Zinc sulfide has a better stabilizing effect in the early stages of composite material preparation, while zinc oxide has a better stabilizing effect in the later stages. Therefore, using a mixture of zinc oxide and zinc sulfide in a mass ratio of 1:1 as a stabilizer can effectively improve the stability of the composite material and extend its service life.
[0039] According to an embodiment of the present invention, the antioxidant is a hindered phenolic antioxidant and / or a phosphite antioxidant. The use of the antioxidant can effectively improve the processing stability of the composite system and resist yellowing and degradation of the composite material.
[0040] According to an embodiment of the present invention, the heat-resistant agent is montmorillonite. The montmorillonite has an aspect ratio > 200 and a specific surface area > 700 m². 2 / g. This invention selects montmorillonite as a heat-resistant agent. Its layered structure's barrier effect prevents the diffusion of heat and degradation products, effectively improving the stability of bamboo fiber at high temperatures and avoiding its decomposition during high-temperature processing due to the poor thermal stability of bamboo fiber. Specifically, during the extrusion process of the composite material, the montmorillonite forms a "brick wall" staggered arrangement in the composite system, creating a tortuous heat conduction path. When heat wants to transfer to the surface of the bamboo fiber, it must bypass the obstruction of the montmorillonite layers, which significantly reduces the heat conduction rate. Simultaneously, volatile substances (such as formaldehyde and acetic acid) produced by the decomposition of bamboo fiber at high temperatures are adsorbed by the montmorillonite layers, delaying their diffusion into the composite system and thus inhibiting the chain degradation reaction. In summary, the montmorillonite can provide better heat resistance for the composite material.
[0041] According to an embodiment of the present invention, the compatibilizer is maleic anhydride-grafted POE. Since PC resin is a polar polymer, while ASA resin is non-polar or weakly polar, when PC resin and ASA resin are directly blended, the resulting composite material has poor interfacial compatibility, easily leading to phase separation and a significant decrease in the mechanical properties of the composite material. The present invention preferably incorporates maleic anhydride-grafted POE as a compatibilizer, wherein maleic anhydride, as a polar group, can enhance the interfacial adhesion between PC resin and ASA resin, and the POE elastomer segments can disperse stress, improving the impact toughness of the composite material.
[0042] According to an embodiment of the present invention, the melt index of the maleic anhydride-grafted POE at 190°C / 2.16 kg is 0.5-2.0 g / 10 min, for example, 0.5 g / 10 min, 0.8 g / 10 min, 1.0 g / 10 min, 1.2 g / 10 min, 1.5 g / 10 min, 1.8 g / 10 min or 2.0 g / 10 min; the grafting rate of the maleic anhydride-grafted POE is 1.0%-1.3%, for example, 1.0%, 1.1%, 1.2% or 1.3%.
[0043] According to an embodiment of the present invention, the maleic anhydride-grafted POE is prepared by a method known in the art, or is obtained through commercial purchase, such as maleic anhydride-grafted POE products with the grades N216, N416, N493, and N525 purchased from Dow Chemical Company, or maleic anhydride-grafted POE products with the grades MA0750, MA1010, and MA8510 purchased from Mitsui Chemicals Company, etc.
[0044] According to an embodiment of the present invention, the processing aid is a low molecular weight acrylate copolymer. Preferably, the low molecular weight acrylate copolymer is a copolymer of methyl methacrylate and acrylate.
[0045] According to an embodiment of the present invention, the weight average molecular weight of the copolymer of methyl methacrylate and acrylate is 300,000 to 500,000, for example, 300,000, 350,000, 400,000, 450,000 or 500,000.
[0046] According to an embodiment of the present invention, the low molecular weight acrylate copolymer is prepared by a method known in the art, or is obtained through commercial purchase, such as low molecular weight acrylate copolymer products of the PARALOID series purchased from Dow Chemical Company (e.g., MMA-BA copolymer resins of grades B66, B72, B82, A21, etc.), low molecular weight acrylate copolymer products of grades P-201 and P301 purchased from Formosa Plastics Chemical Company, and low molecular weight acrylate copolymer products of grades WAC-602 and WAC-501 purchased from Wanhua Chemical Company, etc.
[0047] According to an embodiment of the present invention, when the processing aid is a low molecular weight acrylate copolymer, it effectively promotes the melting of ASA resin, improves the melt flowability of the composite system, and at the same time reduces the processing temperature, significantly reducing the risk of thermal decomposition of bamboo fiber.
[0048] According to an embodiment of the present invention, the composite material comprises PC resin, ASA resin, and SAN resin. Since both PC resin and ASA resin contain siloxane structures, they not only possess high low-temperature impact strength but also can form stable -Si-O-Si- covalent bonds with the hydroxyl groups (-OH) on the surface of bamboo fibers, enhancing the interfacial bonding between the bamboo fibers and the resin matrix (composed of PC resin, ASA resin, and SAN resin). Furthermore, the silane embeddings are uniformly distributed within the resin backbone, resulting in more thorough and robust interfacial coverage. Compared to traditional methods involving the addition of silane coupling agents, the selection of PC resin, ASA resin, and bamboo fibers in this invention offers advantages such as greater stability, higher efficiency, and simplified processing. Furthermore, the SAN resin is preferably a low molecular weight acrylonitrile-styrene copolymer resin with a number-average molecular weight of 100,000-200,000. This effectively ensures the melt flowability of the composite system, improving the dispersion effect of bamboo fibers and silica aerogel while reducing the processing temperature, thereby minimizing the risk of bamboo fiber degradation at high temperatures.
[0049] The present invention also provides a method for preparing the above-mentioned environmentally friendly noise-reducing PC / ASA audio composite material, the method comprising the following steps: 1) PC resin, ASA resin, SAN resin, stabilizer, antioxidant, heat resistant agent, compatibilizer and processing aid are added to a mixing tank according to the weight parts and mixed to obtain a premix; 2) Add the premix from step 1) to the main feed port of the twin-screw extruder, and add the acetylated bamboo fiber and silicone aerogel from the side feed port 1 and the side feed port 2 of the twin-screw extruder, respectively. Then, extrusion granulation is performed to obtain the composite material.
[0050] According to an embodiment of the present invention, in step 1), the mixing temperature is room temperature.
[0051] According to an embodiment of the present invention, in step 2), the twin-screw extruder has 10 zones, wherein the side feed port 1 of the twin-screw extruder is located in zone 5, and the side feed port 2 of the twin-screw extruder is located in zone 7.
[0052] According to an embodiment of the present invention, in step 2), the temperature of the extrusion granulation is 190-230°C, for example, 190°C, 200°C, 210°C, 220°C or 230°C; and the rotation speed of the extrusion granulation is 150-200 rpm.
[0053] This invention also provides the application of the above-mentioned environmentally friendly noise-reducing PC / ASA audio composite material in the audio field.
[0054] The beneficial effects of this invention are: (1) Excellent resistance to photo-thermal aging: This invention uses PC resin / ASA resin as the base material, combining the thermal stability of PC resin and the photo-aging resistance of ASA resin. PC resin / ASA resin not only has high strength and impact resistance, effectively resisting external collisions and friction, but also has excellent weather resistance. Whether in high temperature, low temperature, humid environment or strong ultraviolet radiation environment, PC resin / ASA resin can maintain stable performance and is not prone to deformation, fading, embrittlement and other problems. At the same time, by acetylation treatment of bamboo fiber, the hydroxyl groups are partially replaced by acetyl groups, which significantly improves the thermal stability of bamboo fiber; at the same time, montmorillonite with a lamellar structure is used as a heat-resistant agent to block the transfer of heat and the diffusion of degradation products, thereby improving the stability of bamboo fiber.
[0055] (2) Excellent sound absorption and noise reduction effect: The composite of silica aerogel and bamboo fiber adjusts the damping, enabling the composite material to maintain excellent performance in both high and low frequency regions, making the sound warmer and richer, reducing the "cold and hard" feeling common in plastic materials, and creating a natural sound quality similar to that of a wooden speaker. At the same time, it gives the shell a wood-like texture and grain, enhancing the overall grade of the speaker and satisfying consumers' pursuit of aesthetics and quality. Specifically, the nanoscale pore size of silica aerogel is much smaller than the high frequency wavelength (above 2000Hz), resulting in more complete dissipation of high frequency sound energy and a more prominent sound insulation effect for high frequency sounds. The grooves and micropores on the surface of bamboo fiber are larger, resulting in excellent performance in the mid and low frequencies. This invention is the first to use silica aerogel and bamboo fiber composite to construct a sound absorption and noise reduction system, optimizing the response to sound waves of different frequencies through damping adjustment, creating a fuller and more realistic sound field. Detailed Implementation
[0056] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0057] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0058] The acetylated bamboo fibers used in the following examples and comparative examples were prepared by the following method: (1) First, remove bamboo chips, dust and other impurities from the bamboo fiber. Then, rinse the bamboo fiber with deionized water 3-5 times until the rinsing solution is neutral. Dry the cleaned bamboo fiber in an oven at 60℃ for 24 hours to obtain bamboo fiber with a moisture content of ≤5%. (2) The dried bamboo fiber with a moisture content of ≤5%, acetic anhydride and p-toluenesulfonic acid are mixed at a mass ratio of 1:6:0.02 at a speed of 300-500 rpm. After reacting at 70°C for 10 hours under nitrogen protection, deionized water with a total volume of 2-3 times the reaction solution is added to terminate the reaction. (3) Rinse the bamboo fiber repeatedly with deionized water until the pH of the filtrate is 6-7, and then dry it in a vacuum oven at 60℃ for 12 hours to obtain acetylated bamboo fiber with a degree of acetylation (DS) of 0.6.
[0059] The preparation methods of the environmentally friendly noise-reducing PC / ASA audio composite materials in Examples 1-4 and Comparative Examples 1-5 below include the following steps: 1) PC resin (PC resin of grade EXL1414 purchased from SABIC), ASA resin (ASA resin of grade LP2083 purchased from Guangzhou Shangneng Company), SAN resin (SAN resin of grade 81HF purchased from LG Chem Company), stabilizer (a mixture of zinc oxide and zinc sulfide in a mass ratio of 1:1), antioxidant (antioxidant purchased from BASF 1010), heat resistant agent (montmorillonite of grade DK32B purchased from Zhejiang Fenghong Company), compatibilizer (maleic anhydride grafted POE of grade N216 purchased from Dow Chemical Company), and processing aid (polymer of methyl methacrylate and acrylate of grade P-201 purchased from Formosa Plastics Chemical Company) were added to a stirred tank according to the weight parts and mixed at room temperature to obtain a premix. 2) Add the premix from step 1) to the main feed port of the twin-screw extruder. Add the acetylated bamboo fiber (acetylated bamboo fiber prepared by the above method with a degree of acetylation (DS) of 0.6) and the silica aerogel (HUALU AG-DH silica aerogel from China Chemical Hualu New Materials Co., Ltd.) from the side feed port 1 (located in zone 5 of the twin-screw extruder) and the side feed port 2 (located in zone 7 of the twin-screw extruder), respectively. Then, extrusion granulation is carried out at 190-230℃ and 150-200rpm to obtain the composite material.
[0060] Table 1. Formulations of composite materials for the preparation examples and comparative examples.
[0061] Test standards and methods: 1) Tensile strength: Tested according to ASTM D638 standard at a test speed of 50 mm / min.
[0062] 2) Flexural modulus: Tested according to ASTM D790 standard at a test speed of 2 mm / min.
[0063] 3) Notched impact strength at 23°C: Tested according to ASTM D256 standard, with a sample thickness of 3.2 mm and a test condition of 23°C.
[0064] 4) -30℃ Notched Impact Strength: After placing the specimen at -30℃ for 4 hours, test it within 2 seconds according to ASTM D256 standard.
[0065] 5) Heat distortion temperature: Tested according to ASTM D648 standard, test conditions are 1.82 MPa and heating rate is 120℃ / h.
[0066] 6) Color L value: According to CIE Lab standard testing, the lower the L value, the darker the color.
[0067] 7) Noise reduction performance: The transmission loss was tested according to GB / T 19889.1 (standing wave tube method). The sample thickness was 2.5mm, the sound frequency range was 200Hz-4000Hz, and the unit was dB. The larger the value, the better the sound absorption effect.
[0068] Table 2 Test results of composite materials in the examples and comparative examples
[0069] Table 3. Sound transmission loss tests of composite materials in the examples and comparative examples.
[0070] A comparison of Example 1 and Comparative Example 1 shows that when acetylated bamboo fiber is used entirely without silicone aerogel, the high bamboo fiber content results in a more reinforced composite material with slightly improved rigidity and toughness, but a lower L-value and a darker color. Regarding sound absorption, Comparative Example 1 shows a decrease in sound absorption at mid-to-high frequencies (1500-4000Hz), with the difference increasing at higher frequencies compared to Example 1, indicating that silicone aerogel has a significant effect on high-frequency sound absorption and noise reduction.
[0071] A comparison of Example 2 and Comparative Example 2 shows that when silicone aerogel is used entirely without acetylated bamboo fiber, the rigidity of the resulting composite material is significantly reduced, while the toughness is significantly improved, the L-value is larger, and the color is noticeably whiter. Regarding sound absorption, Comparative Example 2 shows a decrease in sound absorption at mid-to-low frequencies (200-1500Hz), with the difference increasing as the frequency decreases, indicating that acetylated bamboo fiber has a significant effect on low-frequency sound wave absorption and noise reduction.
[0072] A comparison of Example 3 and Comparative Example 3 shows that without the addition of the heat-resistant agent montmorillonite, the heat resistance of bamboo fiber deteriorates, leading to degradation during high-temperature extrusion. This results in a weakened reinforcing effect, decreased tensile and flexural heat deformation properties, a lower L-value, and a significantly darker color in the composite material. Regarding sound absorption, the charring and degradation of bamboo fiber reduces the number of micropores, preventing sound waves from propagating and dissipating within the pores, thus reducing the sound absorption effect of the composite material.
[0073] A comparison of Example 4 and Comparative Example 4 shows that when using untreated bamboo fiber, the bamboo fiber degrades severely during high-temperature extrusion, resulting in a poorer reinforcing effect of the composite material, a significant decrease in mechanical properties and heat deformation properties, and a noticeable blackening of the color. Regarding sound absorption, a large amount of bamboo fiber is charred and carbonized, losing its ability to attenuate and consume sound wave energy, reducing sound transmission loss, and thus significantly decreasing the sound absorption performance of the composite material.
[0074] A comparison of Example 1 and Comparative Example 5 shows that when bamboo fiber and silicone aerogel reinforcement are not treated with acetylation, the rigidity and thermal deformation of the composite material decrease significantly while the toughness increases significantly, and the color becomes whiter. The sound transmission loss differs greatly from that of Examples 1-4, indicating the worst sound absorption and noise reduction effect.
[0075] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An environmentally friendly noise-reducing PC / ASA audio composite material, wherein, The composite material comprises the following components in parts by weight: 30-40 parts by weight of PC resin, 20-30 parts by weight of ASA resin, 10-20 parts by weight of SAN resin, 5-10 parts by weight of silicone aerogel, 15-25 parts by weight of bamboo fiber, 0.2-0.5 parts by weight of stabilizer, 0.2-0.5 parts by weight of antioxidant, 1-2 parts by weight of heat resistant agent, 3-5 parts by weight of compatibilizer, and 0.5-1 parts by weight of processing aid.
2. The environmentally friendly noise-reducing PC / ASA audio composite material according to claim 1, wherein, The PC resin is a silicone copolymer bisphenol A type polycarbonate resin, wherein the silicon content by mass is 5%-10%; And / or, the melt index of the PC resin at 300℃ / 1.2kg is 8-20g / 10min. Preferably, the ASA resin is an organosilicon-modified acrylonitrile-styrene-acrylate graft copolymer, wherein the mass percentage of acrylate is 50-70%. Preferably, the SAN resin is an acrylonitrile-styrene copolymer resin, wherein the mass percentage of acrylonitrile is 20%-30% and the mass percentage of styrene is 70%-80%. And / or, the number-average molecular weight of the SAN resin is 100,000 to 200,000; And / or, the melt index of the SAN resin at 220°C / 10kg is 50-70 g / 10 min.
3. The environmentally friendly noise-reducing PC / ASA audio composite material according to claim 1 or 2, wherein, The silica aerogel is a silica aerogel; And / or, the pore size of the silica aerogel is 20-50 nm, and the porosity of the silica aerogel is 90-95%.
4. The environmentally friendly noise-reducing PC / ASA audio composite material according to any one of claims 1-3, wherein, The bamboo fiber is acetylated bamboo fiber, wherein the degree of acetylation (DS) is 0.5-0.8; And / or, the length of the bamboo fiber is 1-5 mm; the diameter of the bamboo fiber is 10-50 μm.
5. The environmentally friendly noise-reducing PC / ASA audio composite material according to claim 4, wherein, The acetylated bamboo fiber was prepared by the following method: (1) Remove impurities from bamboo fibers, wash and dry until the moisture content of bamboo fibers is ≤5%; (2) Mix the dried bamboo fiber, acetic anhydride and p-toluenesulfonic acid and react them; after reacting for a period of time, add deionized water to terminate the reaction; (3) The bamboo fibers after the reaction are washed and dried with deionized water to prepare the acetylated bamboo fibers. Preferably, in step (2), the mass ratio of bamboo fiber to acetic anhydride is 1:5-12; And / or, in step (2), the mass ratio of the bamboo fiber to p-toluenesulfonic acid is 1:0.01-0.05; And / or, in step (2), the reaction is carried out under nitrogen protection; And / or, in step (2), the temperature of the reaction is 60-90°C; the reaction time is 5-12 hours.
6. The environmentally friendly noise-reducing PC / ASA audio composite material according to any one of claims 1-5, wherein, The stabilizer is a mixture of zinc oxide and zinc sulfide, preferably a mixture of zinc oxide and zinc sulfide in a mass ratio of 1:
1. Preferably, the antioxidant is a hindered phenolic antioxidant and / or a phosphite antioxidant. Preferably, the heat-resistant agent is montmorillonite; And / or, the aspect ratio of the montmorillonite is >200, and the specific surface area of the montmorillonite is >700 m². 2 / g.
7. The environmentally friendly noise-reducing PC / ASA audio composite material according to any one of claims 1-5, wherein, The compatibilizer is maleic anhydride-grafted POE. And / or, the melt index of the maleic anhydride-grafted POE at 190℃ / 2.16kg is 0.5-2.0g / 10min; the grafting rate of the maleic anhydride-grafted POE is 1.0%-1.3%. Preferably, the processing aid is a low molecular weight acrylate copolymer, which is a copolymer of methyl methacrylate and acrylate. And / or, the weight average molecular weight of the copolymer of methyl methacrylate and acrylate is 300,000 to 500,000.
8. A method for preparing the environmentally friendly noise-reducing PC / ASA audio composite material according to any one of claims 1-7, the method comprising the following steps: 1) PC resin, ASA resin, SAN resin, stabilizer, antioxidant, heat resistant agent, compatibilizer and processing aid are added to a mixing tank according to the weight parts and mixed to obtain a premix; 2) Add the premix from step 1) to the main feed port of the twin-screw extruder, and add the acetylated bamboo fiber and silicone aerogel from the side feed port 1 and the side feed port 2 of the twin-screw extruder, respectively. Then, extrusion granulation is performed to obtain the composite material.
9. The preparation method according to claim 8, wherein, In step 2), the twin-screw extruder has 10 zones, of which the side feed port 1 of the twin-screw extruder is located in zone 5 and the side feed port 2 of the twin-screw extruder is located in zone 7. Preferably, in step 2), the extrusion granulation temperature is 190-230℃; the extrusion granulation speed is 150-200 rpm.
10. The application of the environmentally friendly noise-reducing PC / ASA audio composite material according to any one of claims 1-7 in the audio field.